A retrospective analysis of bone loss in tenofovir-emtricitabine therapy for HIV PrEP. (December 2022) - Chang, Joseph; Do, Duy; Delgado, Hector; Kanimian, Natalie; Huynh, An
Background: Tenofovir-Emtricitabine (TDF-FTC) is known to cause bone loss in about 1–3% of HIV treated patients. Current studies lack evidence in minority groups and long-term bone loss effects in PrEP patients. Setting: To address the risk of osteopenia/osteoporosis in patients on TDF-FTC therapy for HIV PrEP and to address the breakthrough incidence of HIV. Methods: A retrospective analysis was performed in Kaiser Permanente patients from 2012–2021. Patients on TDF-FTC for PrEP without any prior history of osteopenia/osteoporosis ( N = 7698) were analyzed to determine the relationship between PrEP adherence and osteopenia/osteoporosis. Descriptive statistics and Cox proportional hazards model were used to compare and analyze patient characteristics between those who developed osteopenia/osteoporosis and those who didn't. Results: 3% were found to have osteopenia/osteoporosis. Patients who developed osteopenia/osteoporosis were more likely to have a proportion of days covered (PDC) ratio ≥90%, older, had history of Hep B, DM, CVD, CKD, hypertension, and baseline eGFR ≥90 mL/min/1.73 m 2 . Kaplan-Meier curve showed the event-free rate of osteopenia/osteoporosis decreased with time, with a greater reduction in patients with high adherence. Survival analysis showed only PDC of ≥90% was significantly associated with the risk of osteopenia/osteoporosis when adjusted. No incidence of HIV infection was detected. Conclusions: This retrospective cohort analysis showed that TDF-FTC offered superior PrEP protection. Although high PrEP adherence ensured protection from HIV infection, it was significantly associated with a higher risk of developing osteopenia/osteoporosis. These findings suggest that routine check-ups for osteopenia/osteoporosis may be needed.